The Influence of Problem-Based Learning and Motivation On Learning Outcomes - Tri Herwidyatmono; Bachtiar Sjaiful Bachri; Andi Kristanto (Jurnal Studi Guru dan Pembelajaran, 2024)
This study aims to examine the impact of the Problem-Based Learning (PBL) model and motivation on the learning outcomes of 11th-grade students at SMA Negeri 3 Bojonegoro in the subject of Pendidikan Kewarganegaraan (PKN). The sample consisted of two classes: an experimental class using PBL and a control class using the discovery learning method. In general, students with higher motivation tended to have better learning outcomes. The Two-Way ANOVA analysis results showed that learning motivation (F(3, 65) = 33.481, p < 0.001) and teaching methods (F(1, 65) = 4.069, p = 0.048) significantly influenced learning outcomes. However, there was no significant interaction between motivation and teaching methods (F(2, 65) = 0.840, p = 0.436). The model explained about 69.3% of the variation in student learning outcomes (R² = 0.693), indicating that motivation and teaching methods together significantly contribute to student learning outcomes.